2021
DOI: 10.31254/jmr.2021.7509
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Tobacco Cessation Program for Pregnant Women in an Antenatal Care Setting: A Mixed Methods Study

Abstract: Background: Tobacco use during pregnancy has deleterious effects on the woman and child. Many pregnant women make quit attempts but few are successful. Antenatal Care (ANC) services create an opportunity to identify tobacco users and provide cessation services. The aim of the study was to assess the feasibility of implementing LifeFirst tobacco cessation services for pregnant women attending ANC clinic. Methods: We used mixed methods study design. All pregnant women attending ANC services during one year were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Some women initiate tobacco use during their pregnancy due to craving, to relieve stress and anxiety related to pregnancy or to suppress vomiting during pregnancy 6 . Others believe that it relieves ‘labour pain’ and body pain and strengthens teeth during pregnancy 5 7 14 . One study reported that women use tobacco because they believe that it relieves gastric problems and body pain, suppresses hunger, eases stress, relieves tooth ache and is customary to use in special family functions such as weddings and after eating non-vegetarian meals.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Some women initiate tobacco use during their pregnancy due to craving, to relieve stress and anxiety related to pregnancy or to suppress vomiting during pregnancy 6 . Others believe that it relieves ‘labour pain’ and body pain and strengthens teeth during pregnancy 5 7 14 . One study reported that women use tobacco because they believe that it relieves gastric problems and body pain, suppresses hunger, eases stress, relieves tooth ache and is customary to use in special family functions such as weddings and after eating non-vegetarian meals.…”
Section: Resultsmentioning
confidence: 99%
“…In a study based in an antenatal care setting, an interview with a tobacco cessation counsellor revealed that the women who attended counselling sessions provided either the wrong contact number or that of their spouses’, which made it difficult to establish effective contacts for further follow ups and telephonic counselling. Some even hid their tobacco habits from other family members and did not want to be contacted at home, thereby leading to high attrition rates from counselling sessions 7 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations